PENGARUH KREDIT TERHADAP PENDAPATAN PETANI KOPI ARABIKA DI KABUPATEN ACEH TENGAH PROVINSI ACEH - Nurul Iski; Nunung Kusnadi; Harianto Harianto (School of Business, Bogor Agricultural University (SB-IPB), 2016)
Agric finance is one of the important components in the development of coffee plant which is one of the main export commodities of Indonesia. This research aims to 1) identify the factors affecting credit access to formal sources of finance by the farmers, and 2) analyze the effects of credit on the farmer income. The study was conducted in the Arabica coffee production center at Aceh Tengah district. Data were collected from 73 farmers by the stratified random sampling. The data analysis was conducted using the probit model, and the results showed that the factors affecting farmers’ access to credit include age, dummy of creditor‘s visit and farmers' knowledge. Using simultaneous equation model (2SLS), the estimation results showed that credit has positively increased production and food consumption of organic Arabica coffee of the farmers. Correspondingly, the simulation results showed that the increase in production and consumption of food will increase the productivity of the labor in the family, and this is the dominant input in organic Arabica coffee farming that will increase the farmers' income.Keywords: organic Arabica coffee, credit, simultaneous (2SLS), farmers’ income, probit